Comovement and contagion in commodity markets - Dony Abdul Chalid; Rangga Handika (Cogent Economics & Finance, 2022)
This article investigates comovement and contagions in the commodities markets. We examine the comovement by analyzing the unconditional correlation coefficients. We document that commodities tend to partially integrate. We perform contagion tests by identifying coexceedances and estimating multinomial logit to explain the joint occurrence of those coexceedances. We document that commodities price changes tend to affect the probability of both positive and negative coexceedances. Overall, we conclude that there are comovement and contagions among commodities. However, the degrees of comovement and contagion are different among commodities and between positive and negative extreme returns. The contagion among commodities is asymmetric.
Keywords: 330; Commodity markets; Correlation; Comovement; Contagion; Multinomial logit